Feldspar for Potassium, Fertilisers, Catalysts and Cement - Rajagopala Rao, J.; Nayak, R.; Suryanarayana, A. (Asian Journal of Chemistry, 2010)
Feldspar for Potassium, Fertilisers, Catalysts and Cement.